El scoring de crédito en la línea de consumo de la cooperativa de ahorro y crédito “13 De Abril”, del cantón Ventanas, provincia Los Ríos, año 2014 - Carriel Cabrera, María Elena (2015)
The Credit Cooperative “April 13” has the credit portfolio, which is the primary creator of the revenue, so it is necessary to take proper control of it, to avoid the credit risk and there is no deficit in the corporation. That is why this research is very important because it helps as a guide for a perfect and proper analysis of applicants credit members, with the credit Scoring as a tool that approves or rejects the granting of credit in the consumer line borrowers. The main objective of this work is to obtain results in a credit Scoring system in the consumer line that will serve as a guide for proper analysis of the borrower and must have characteristics for proper operation, because it is suitable for analyzing quickly and safe a lot of credit applications, verifying the approval and rejection of it. This degree work is divided into three chapters, which are detailed below: Chapter I: The topic is shown, Background, contextualization of the problem which is divided into (macro, micro and meso), the prognosis, Sub problem, problem formulation, delimitation of the problem, problem tree, justification, Objectives and theoretical framework is divided into Reference framework that is the history of the Cooperative, Geo Reference Framework is the location, Legal Framework, are the laws to which the cooperative is governed, Scientific theory are definitions taken from several authors, the same as contribute to the development of this investigative work. Chapter II: In this chapter there is data collection, analysis and interpretation of results, hypothesis testing, conclusions and recommendations is reported. Chapter III: The proposal under study which is based on the 5 ”C” and implementing the credit Scoring system applied in the credit line will use the same as for fitting of economic resources is detailed.